(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
This research aims to find out whether Socioemotional Wealth (SEW) influences entrepreneurial success specifically for family companies. Information about SEW and entrepreneurial success from 100 family companies located in Padang City, West Sumatra was gathered using quantitative methods. Smart PLS was employed to process data with research locations. The research results show that SEW has an influence on entrepreneurial success. The influence of SEW on entrepreneurial success is 0.241 or 21.4 per cent, while other factors have not been carried out in this research. The slight influence of SEW on entrepreneurial success is also influenced by the Minang ethnic system and culture which adheres to matrilinealism. The limitation of this research is that there are still few respondents, and further research can use a larger number of respondents by adding other related variables such as culture, entrepreneurial resilience and other variables.